The role of icosapent ethyl in cardiovascular risk reduction. (September 2021) - Goldenberg, Ronald M.; Cheng, Alice Y.Y.; Gilbert, Jeremy D.; Lonn, Eva M.; Pedersen, Sue D.; Verma, Subodh
Abstract : Purpose of review: Elevated levels of triglycerides, independent of low-density lipoprotein cholesterol (LDL-C) levels and statin therapy, are associated with heightened cardiovascular risk. Recent findings: Mixed omega-3 fatty acid formulations, which contain varying amounts of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), lower triglycerides levels but trial results with omega-3 fatty acids combinations have generally been neutral for cardiovascular outcomes. In contrast, the REDUCE-IT trial with icosapent ethyl (IPE), a highly purified ethyl ester of EPA, demonstrated reduced cardiovascular risk in individuals with established atherosclerotic cardiovascular disease or diabetes with at least one additional risk factor, despite having relatively well controlled LDL-C levels but triglycerides at least 135 mg/dl while on statin therapy. IPE offers an important new avenue for cardiovascular risk management in statin-treated individuals with elevated triglycerides. Summary: This review summarizes the results from outcome trials conducted with omega-3 fatty acids, differentiating between those with combinations of EPA/DHA and those with pure EPA, as well as imaging and preclinical data that help explain the different cardiovascular efficacy observed. A list of frequently asked questions with evidence-based responses is provided to assist our colleagues and their patients in the shared-decision process when considering if IPE is appropriate for cardiovascular risk reduction.